2017
DOI: 10.1186/s12966-017-0508-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring parent-reported barriers to supporting their child’s health behaviors: a cross-sectional study

Abstract: BackgroundParents can influence the health behaviors of their children by engaging in supportive behaviors (e.g., playing outside with their child, limiting recreational screen time). How, and the extent to which parents engage in supportive behaviors may be influenced by perceived barriers. The purpose of this study is to explore whether the frequency, and types, of barriers to providing parental support are dependent on the type of child health behavior being supported (i.e., physical activity, recreational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
(44 reference statements)
1
25
1
Order By: Relevance
“…Previous studies also reported that parenting style was associated with children’s PA [ 14 , 15 , 16 ]. For example, in a computer-assisted telephone interview survey in Ontario, parents reported more parent level and environmental level barriers to support child PA compared to other behaviors such as reducing recreational screen time, encouraging healthy eating, and ensuring good sleep habits [ 36 ]. We therefore propose that more studies on parenting style are needed to identify the relationship between parenting style and PA in children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that parenting style was associated with children’s PA [ 14 , 15 , 16 ]. For example, in a computer-assisted telephone interview survey in Ontario, parents reported more parent level and environmental level barriers to support child PA compared to other behaviors such as reducing recreational screen time, encouraging healthy eating, and ensuring good sleep habits [ 36 ]. We therefore propose that more studies on parenting style are needed to identify the relationship between parenting style and PA in children.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen’s kappa was calculated to establish inter-rater reliability, and exceeded the acceptable agreement ( k = 0.71), so a single coder completed the remainder of the coding. This approach to coding has previously been used to code barriers to supporting child health behaviours, collected in a similar manner [ 70 ]. Given the granularity with which the barriers were coded through this process, individual barriers were aggregated up to one of four barrier types for analysis, informed by the socio-ecological perspective: child-level, parent-level, facility-related, and environmental ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…There is no any study in Iranian population in this field. In literature review, we found few studies about parental perceived barriers to healthy diet and PA.[ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%